SISTEM INFORMASI KELAYAKAN KREDIT BERBASIS WEB MENGGUNAKAN METODE AHP (ANALYTICAL HIERARCHY PROCESS) - Safia Rahmatulailah; Hardiansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Technology encourages all aspects of life to grow. One of them has to be Has a strategy in the management of information systems to process data, Of obtaining, organizing, storing and manipulating data in various ways to generate The information of quality, which is relevant, is accurate and timely which is used for The decision maker. Credit is a financial facility that allows people or businesses to borrow money To buy a product and pay it back within a set period of time.In the performance of financing or credit giving, the thing to avoid is poor credit. The rupiah fell to rp9,100 per dollar in the Jakarta interbank spot market on Tuesday morning as investors bought the local unit Continue payment or mortgage debt from financing or credit given. It can It is because borrowers, or debtors, do not have sufficient funds Pay up, et cetera. To resolve the issues raised above, this made my desire necessary To build web-based information systems and store the data into databases Using ahp (analytical treatments process) methods of development A multicriteria based decision making Others in decision-making approach systems, where decision-makers make the effort.